Analisis Kebijakan Perlindungan Nasabah Pada Bank Digital Syariah di Indonesia - Firmanda, Muhammad Esza Maulana; Efendi, Taufik Kukuh; Alfarisy, Fathor Rozy; Javantara, Alfado Chievo; Indrarini, Rachma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study analyzes customer protection policies in Islamic digital banks in Indonesia within the framework of Islamic economics. The research focuses on evaluating the effectiveness of policies implemented to protect customers, particularly in the areas of personal data security, information transparency, and dispute resolution mechanisms. Using a literature review method, the study finds that most Islamic digital banks in Indonesia have implemented protective measures, including data encryption technology, provision of product information, and customer complaint systems. However, challenges remain, such as limited customer understanding of Islamic terminology and the need for improved efficiency in complaint resolution. This study recommends enhancements in data security education, simplification of language, and utilization of technology in customer service. The findings are expected to assist Islamic digital banks in improving the quality of customer protection and strengthening trust in Islamic digital banking services that align with Sharia principles.